INTEGRATING BIOINFORMATICS AND ECOLOGICAL DATA TO PREDICT THE IMPACT OF HABITAT LOSS ON SPECIES DISTRIBUTION - Miguel Torres (Modern American Journals, 2025)
Habitat loss is one of the most significant drivers of biodiversity decline, affecting species' survival and distribution. Predicting the potential impacts of habitat loss on species requires the integration of various data sources, including ecological and genomic information. Bioinformatics tools and ecological modeling can offer powerful methodologies for assessing how habitat changes influence species distribution, genetic diversity, and adaptive capacity. This paper explores the potential of combining bioinformatics, genomic data, and ecological models to predict the effects of habitat loss on biodiversity. We present a framework that utilizes species distribution models (SDMs) integrated with genomic data to forecast the vulnerability of species to environmental changes and habitat fragmentation. The implications of these predictions are essential for developing more targeted conservation strategies and informing policy decisions aimed at preserving biodiversity in the face of increasing anthropogenic pressures.
Keywords: Habitat Loss, Bioinformatics, Ecological Data, Species Distribution Models, Biodiversity, Genomic Data, Conservation, Environmental Change, Ecological Modeling, Habitat Fragmentation